Mobile Solar Power Plant (PLTS Mobile) for BASARNAS Operational Area - Muhammaad Yusan Naim; Syamsir Syamsir; Muh. Fauzan Suardi (International Journal of Mechanical, Electrical and Civil Engineering, 2025)
Indonesia is a developing country located at the convergence of four tectonic plates, making it highly prone to natural disasters such as earthquakes, tsunamis, landslides, and volcanic eruptions. These frequent disasters highlight the critical need for reliable electricity during emergencies. However, disaster-affected areas often struggle to restore power due to accessibility issues. To address this, alternative energy sources are needed, and Solar Power Plants (PLTS) offer a practical solution. PLTS are easy to implement, depend only on sunlight, and provide clean energy with low carbon emissions. Under clear skies, solar radiation can reach 1,000 Watts per square meter, making it a powerful energy source. Additionally, PLTS systems are adaptable and can be deployed in various formats, including mobile units. This study focuses on designing a Mobile PLTS to support BASARNAS operations in disaster zones. Data collection was conducted using resources from BNPB, BMKG, BASARNAS, and NASA. The analysis includes the geographical characteristics of the site, solar radiation intensity, and the operational dimensions of the BASARNAS Mobile Truck. The study aims to determine the suitable system specifications and estimate the energy production capacity of the Mobile PLTS. The proposed design features 20 solar panels, each with a capacity of 300 Wp, producing an average of 27.70 kWh per day. It also includes 16 batteries for energy storage. The remaining space in the truck can be used for transporting logistics or essential tools, making it a multifunctional unit ideal for disaster response scenarios.